PERAN PENDAMPINGAN PENDIDIKAN SENI BUDAYA DALAM MEMBANGUN CINTA TANAH AIR ANAK-ANAK MIGRAN (STUDI KASUS DI KUALA LUMPUR) - Mohammad Holis; Wawan Rusdianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Arts and culture education plays a strategic role in fostering character and a sense of patriotism, especially for migrant children living abroad. Migrant children often face challenges in maintaining their cultural identity in a multicultural environment. This community service activity aims to provide arts and culture education mentoring as an effort to strengthen national identity and foster patriotism among migrant children in Kuala Lumpur, Malaysia. The mentoring program is implemented through participatory activities such as introducing traditional dances, regional songs, traditional games, and discussions on Indonesian cultural values. The implementation method uses a participatory approach by involving children and parents in each activity session. The results of the activity show an increase in participants' understanding of Indonesian culture, a growing sense of pride in national identity, and increased confidence in children in expressing their native culture. This activity also provides a space for positive social interaction to reduce feelings of alienation and strengthen ties with the homeland. Therefore, arts and culture education mentoring is effective as a medium for strengthening identity and instilling national values ​​in migrant children living abroad.